If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + 3) + -5x = 2(4x + 3) + 3(x + 1) Reorder the terms: 7(3 + 2x) + -5x = 2(4x + 3) + 3(x + 1) (3 * 7 + 2x * 7) + -5x = 2(4x + 3) + 3(x + 1) (21 + 14x) + -5x = 2(4x + 3) + 3(x + 1) Combine like terms: 14x + -5x = 9x 21 + 9x = 2(4x + 3) + 3(x + 1) Reorder the terms: 21 + 9x = 2(3 + 4x) + 3(x + 1) 21 + 9x = (3 * 2 + 4x * 2) + 3(x + 1) 21 + 9x = (6 + 8x) + 3(x + 1) Reorder the terms: 21 + 9x = 6 + 8x + 3(1 + x) 21 + 9x = 6 + 8x + (1 * 3 + x * 3) 21 + 9x = 6 + 8x + (3 + 3x) Reorder the terms: 21 + 9x = 6 + 3 + 8x + 3x Combine like terms: 6 + 3 = 9 21 + 9x = 9 + 8x + 3x Combine like terms: 8x + 3x = 11x 21 + 9x = 9 + 11x Solving 21 + 9x = 9 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 21 + 9x + -11x = 9 + 11x + -11x Combine like terms: 9x + -11x = -2x 21 + -2x = 9 + 11x + -11x Combine like terms: 11x + -11x = 0 21 + -2x = 9 + 0 21 + -2x = 9 Add '-21' to each side of the equation. 21 + -21 + -2x = 9 + -21 Combine like terms: 21 + -21 = 0 0 + -2x = 9 + -21 -2x = 9 + -21 Combine like terms: 9 + -21 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| 9x-6(0)=-72 | | -6(0)+3y=-9 | | 4b-3=9 | | -6x+3(0)=-9 | | -8k^2+20k-8= | | 6x+1-x-13=5x-3+x | | Solve-5x+zy=z+30forz | | -5x+zy=z+30forbz | | (2x+3)=5 | | x^2+26x+85=0 | | 8k^2-20k+8= | | 15x+-3=4x+8 | | 4n+9=6n | | -(x+6)=22x | | x-3+4=4x-21 | | a+6a+3a=550 | | -1-4x=7-5x | | 2x=3x-100 | | (3a+6)(2a-5)=0 | | r=c-st | | 2(a-(1-a))=3(a-1)+8 | | 9(z-1)-2(3z+4)=5 | | 0.2x+12+2x=4.4 | | x/5+1=x/10 | | -13+27x=-5+11x | | -15x=-5(2x-10) | | T(7)=10*7+5 | | 100+3x=260+5x | | 10x+92=2 | | 4-2(5-x)=10 | | 13+7x-7x=17-3x | | 5x+17+3x-9=90 |